Experimental Study of Bubbly-Slug Flow Transition Criteria in an Vertical Circular Tube by Using WMS - Yu, Shimo; Yan, Xiao; Zhou, Lei; Xu, Aiwei; Zhang, Junyi; Gong, Suijun; Zan, Yuanfeng (Frontiers in Energy Research, 2020)
Two-phase flow is an important and common phenomenon in reactor systems, and there are significant differences in the heat and mass transfer characteristics of two-phase flow under different flow patterns. Researchers have proposed a variety of flow pattern transition mechanisms to predict the two-phase flow. But limited by the means of measurement, the critical void fraction for flow pattern transition can’t be determined. Two types of bubbly-slug flow transition criteria in vertical circular tubes are studied in this paper and a wire mesh sensor (WMS) was manufactured to measure the critical void fraction for bubbly-slug transition. One hundred forty-seven visualization tests were carried out for validation.